Determinants of Patient Satisfaction with Health Services - Fitria, Fitria (Genius Journal, 2025)
Introduction: Health services play a crucial role in improving public health, particularly through primary healthcare centers. Patient satisfaction serves as a key indicator of service quality and is influenced by several factors, including performance, facilities, and communication. However, dissatisfaction remains an issue in many healthcare settings. Objective: This study aimed to identify the factors associated with patient satisfaction at the Tiuh Tohou Health Center, Tulang Bawang Regency in 2024. Method: A quantitative analytical survey with a cross-sectional design was used. The population included all patients treated at the health center in 2024 (n=310), from which 175 were selected using purposive sampling. Data were analyzed using the chi-square test to determine relationships between variables. Result: The results showed that performance, facilities, and communication were significantly associated with patient satisfaction. Poor performance increased dissatisfaction likelihood by 48 times (p=0.000; OR=48.417), poor facilities by 2.5 times (p=0.004; OR=2.577), and poor communication by 20 times (p=0.000; OR=20.063). Most patients were over 35 years old, male, had a high school education, were self-employed, and reported dissatisfaction with services received. Conclusion: Patient dissatisfaction at the Tiuh Tohou Health Center is significantly influenced by poor staff performance, inadequate facilities, and ineffective communication. These findings highlight the need for targeted improvements in health worker performance, infrastructure, and patient-provider communication to enhance satisfaction levels and service quality.